Removing barriers to promote human factors & ergonomics education in developing countries - Rabiul, Ahasan; Azmin, Hassan (2015)
Editorial “Human Factors” concerns fall under the purview of “ergonomics” which is associated with occupational health, safety, productivity, and performance management. Human Factors and Ergonomics (HFs/E) movement started when engineers and top level managers realize that industries had to adjust with workers’ psycho-physical and cognitive capabilities to the technological systems in various industries and companies. HFs/E was primarily focused on the country’s workregulated agencies, or on the eوٴort of National Institute of Occupational Safety and Health (NIOSH) to prevent work-related accidents and injuries. Recently, HFs/E issues and concerns drew worldwide public attention. It is also an emerging issue for the design and improvement of products, processes, and operations. Hence, there are siJniٽcant interests in promoting HFs/E programs in university education. Currently, ergonomics related courses are taught in a few universities and colleges. A number of universities in the developing countries are oوٴerinJ diploma program and delivering certiٽcate courses. However, the existing program may not address contemporary and current and local issues of HFs/E and concerns of socio-cultural, economics, and anthropometrics. Currently, it lacks quality assurance and bias in academic policies and procedures.